Phase 1 of the 2005 Commencement ceremony, robing in the Coolidge Room and the drama department's Phase 2 ceremony in Goddard Chapel. Photo 1106 - Ko, Melody (Tufts Archival Research Center, 2008)
Phase 1 of the 2005 Commencement ceremony, robing in the Coolidge Room and the drama department's Phase 2 ceremony in Goddard Chapel.